Auto-contouring of cardiac substructures for Stereotactic arrhythmia radioablation (STAR): A STOPSTORM.eu consortium study - van der Pol, Luuk H G; Blanck, Oliver; Grehn, Melanie; Blazek, Tomáš; Knybel, Lukáš; Balgobind, Brian V; Verhoeff, Joost J C; Miszczyk, Marcin; Blamek, Slawomir; Reichl, Sabrina; Andratschke, Nicolaus; Mehrhof, Felix; et al. (Radiotherapy and oncology, 2025)
BACKGROUND/PURPOSE: High doses to healthy cardiac substructures (CS) in stereotactic arrhythmia radioablation (STAR) raise concerns regarding potential treatment-induced cardio-toxicity. However, CS contours are not routinely created, hindering the understanding of the CS dose-effect relationships. To address this issue, the alignment of CS contouring was initiated within the STOPSTORM consortium. In this study, we developed and evaluated auto-contouring models trained to delineate CS and major vessels in ventricular tachycardia (VT) patients. METHODS: Eight centres provided standard treatment planning computed tomography (CT) and/or contrast-enhanced CT datasets of 55 VT patients, each including 16 CS. Auto-contouring models were trained to contour either large structures or small structures. Dice Similarity Coefficient (DSC), 95 % Hausdorff distance (HD95) and volume ratio (VR) were used to evaluate model performance versus inter-observer variation (IOV) on seven VT patient test cases. Significant differences were tested using the Mann-Whitney U test. RESULTS: The performance on the four chambers and the major vessels (median DSC: 0.88; HD95: 5.8-19.4 mm; VR: 1.09) was similar to the IOV (median DSC: 0.89; HD95: 4.8-14.0 mm; VR: 1.20). For the valves, model performance (median DSC: 0.37; HD95: 11.6 mm; VR: 1.63) was similar to the IOV (median DSC: 0.41; HD95: 12.4 mm; VR: 3.42), but slightly worse for the coronary arteries (median DSC: 0.33 vs 0.42; HD95: 24.4 mm vs 16.9 mm; VR: 1.93 vs 3.30). The IOV for these small structures remains large despite using contouring guidelines. CONCLUSION: CS auto-contouring models trained on VT patient data perform similarly to IOV. This allows for time-efficient evaluation of CS as possible organs-at-risk.
Keywords: senioři; Tachycardia, Ventricular; Organs at Risk; Tomography, X-Ray Computed; Middle Aged; mužské pohlaví; Radiosurgery; ženské pohlaví; Humans; lidé středního věku; plánování radioterapie pomocí počítače; Heart; kritické orgány; počítačová rentgenová tomografie; Female; Aged; radiochirurgie; komorová tachykardie; srdce; lidé; Male; Radiotherapy Planning, Computer-Assisted